2009
DOI: 10.1515/cclm.2009.247
|View full text |Cite
|
Sign up to set email alerts
|

Preeclamptic placental stress and over expression of mitochondrial HSP70

Abstract: Background: Evidence is accumulating that mitochondrial (Mt) oxidative stress plays a role in the pathogenesis of preeclampsia. The current study analyzes the stress levels, energy status and associated enzymatic alteration in placental mitochondria of preeclamptic (ns30) and normotensive (ns35) subjects. Methods: Total Mt stress was measured using dichlorofluorescin (DCFH) oxidant analysis, malondialdehyde (MDA) concentrations, protein carbonyl (PC) concentrations and measurement of nitrite ( ) and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 43 publications
(40 reference statements)
3
24
0
Order By: Relevance
“…The increase in oxidative stress and nitrative stress observed in cord blood RBC in this study is in coherence with the evidence observed till date, thus suggesting their signifi cant role in the pathophysiology of preeclampsia (34). Many studies confi rm that levels of antioxidants are reduced in the sera, placentas and placental mitochondria of preeclamptic women (31,32,35,36). Similarly in the present study, it was noted that the antioxidant status in preeclamptic cord blood RBC was signifi cantly decreased compared with the normotensive sample.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The increase in oxidative stress and nitrative stress observed in cord blood RBC in this study is in coherence with the evidence observed till date, thus suggesting their signifi cant role in the pathophysiology of preeclampsia (34). Many studies confi rm that levels of antioxidants are reduced in the sera, placentas and placental mitochondria of preeclamptic women (31,32,35,36). Similarly in the present study, it was noted that the antioxidant status in preeclamptic cord blood RBC was signifi cantly decreased compared with the normotensive sample.…”
Section: Discussionsupporting
confidence: 91%
“…1), indicating that both yeast species are effective in reducing the ROS-mediated hemolysis in the preeclamptic sample. Studies have demonstrated that oxidative stress is one of the key factors in complicating preeclampsia which results in preterm birth (31). Oxidative stress is the presence of ROS in excess of the buffering capacity of available antioxidants (32).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that oxidative stress is one of the key factor in complicating preeclampsia which results in preterm birth (Padmini et al 2009b;Padmini & Lavanya, 2011;Padmini & Lavanya, 2009a). The first line of defense for oxidative stress is not sufficient enough to combat with the generated stress.…”
Section: Discussionmentioning
confidence: 99%
“…A significant decrease in the expression of HSP70 observed in the present study on addition of tea and mint extracts may be due to the restoration of cell homeostasis by maintaining the antioxidant status. This property is attributed to the flavonoids, polyphenols and minerals present in tea and mint extracts (Padmini et al 2009b;Padmini et al 2008a;Padmini et al 2008b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation